2020
DOI: 10.3390/ijms21239172
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity and Biological Therapies for the Treatment of Sjögren’s Syndrome

Abstract: Sjögren’s syndrome (SS) is a systemic autoimmune disorder affecting approximately 3% of the population in the United States. This disease has a female predilection and affects exocrine glands, including lacrimal and salivary glands. Dry eyes and dry mouths are the most common symptoms due to the loss of salivary and lacrimal gland function. Symptoms become more severe in secondary SS, where SS is present along with other autoimmune diseases like systemic lupus erythematosus, systemic sclerosis, or rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 305 publications
0
23
0
Order By: Relevance
“…In stark contrast to the control SMG, the NOD.B10 sample consisted of reduced numbers of cells that comprise the epithelial cell populations with the NOD.B10 mice having a total of 3,626 epithelial cells (or ~34%) compared to 4,955 epithelial cells (or ~41%) observed in the control glands ( Figure 4 ). This finding is not surprising given that the loss of these cell populations is commonly observed in pSS and has been attributed to the loss of salivary flow in patients ( 76 ). Overall, our scRNA-seq analyses has revealed the degree of cellular heterogeneity and the broad range of cell types associated with pSS diseased state.…”
Section: Resultsmentioning
confidence: 63%
“…In stark contrast to the control SMG, the NOD.B10 sample consisted of reduced numbers of cells that comprise the epithelial cell populations with the NOD.B10 mice having a total of 3,626 epithelial cells (or ~34%) compared to 4,955 epithelial cells (or ~41%) observed in the control glands ( Figure 4 ). This finding is not surprising given that the loss of these cell populations is commonly observed in pSS and has been attributed to the loss of salivary flow in patients ( 76 ). Overall, our scRNA-seq analyses has revealed the degree of cellular heterogeneity and the broad range of cell types associated with pSS diseased state.…”
Section: Resultsmentioning
confidence: 63%
“…The hallmarks of pSS are progressive focal infiltration of immune cells (mainly T and B cells), hypergammaglobulinemia, and the presence of autoantibodies, underscoring the importance of adaptive immunity in SS pathophysiology (62,63). However, recent findings have suggested that innate immunity-especially NK cells-plays a role in SS pathogenesis (64)(65)(66). The relative and total numbers of circulating NK cells and CD56 dim NK cells were lower while the number of CD56 bright NK cells was higher in pSS patients compared to healthy control subjects (67,68).…”
Section: Nk Cells and Sjögren's Syndromementioning
confidence: 99%
“…Results of function analysis using murine SS models have elucidated that 1, 2, and 17 cells are of great significance in the occurrence and development of SS, which play roles in regulating the differentiation, amplification, and functions of self-reactive T and B cells [7][8][9]. Furthermore, inflammatory cytokines balance the epithelial homeostasis and modulates the functions of B and T cells [3]. Ectopic expressions of CXC chemokines (CXCL9, CXCL10, CXCL11, and CXCL13), interleukins (IL-1/2/4/6/10/12/17/ 22/23), IFN-c, and TNF-α occur in the minor salivary glands of SS patients as compared to healthy individuals [10,11].…”
Section: Introductionmentioning
confidence: 99%